Penyuluhan Pentingnya Tablet Fe Untuk Ibu Hamil Di Desa Pattallassang Kabupaten Bantaeng - Nelly Nugrawati; Ayu Wijaya; Andi Muhammad Adam; Siti Alfa; Nur Ekawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Anemia is one of the causes of maternal death. The prevalence of pregnant women in Indonesia is 37.1%. The low level of knowledge of pregnant women affects If pregnant women experience nutritional and iron deficiencies during pregnancy it will cause problems, both for the mother and the fetus they contain, namely anemia, bleeding, and the mother's weight does not increase normally. Lack of nutrition can also affect the delivery process which can lead to difficult and long labor, premature birth, bleeding after delivery, lack of nutrition can also affect fetal growth and can cause miscarriage, abortion, congenital defects and low birth weight of the fetus. Fe becomes limited and has an impact on the occurrence of iron deficiency. The better the knowledge of pregnant women, the better in absorbing information, especially about Fe tablets. If pregnant women experience a lack of nutrients and iron during pregnancy, it will cause problems, both for the mother and the fetus they contain, namely anemia, bleeding, and the mother's weight does not increase normally. Giving Fe tablets is one of the most effective prevention and control strategies for anemia in increasing hemoglobin levels and can reduce the prevalence of anemia in pregnant women by 20-25%. The method used is counseling. Counseling about Fe tablets is very effective in overcoming the side effects that are felt after consuming Fe tablets. The results of the service showed an increase in knowledge and compliance of pregnant women in consuming Fe tablets as an effort to prevent iron deficiency anemia in pregnant women.